Study of thermal decomposition of ignition temperature of bagasse, coal and their blends - Mortari, Daniela Andresa; Ávila, Ivonete; Santos, A. Moreira; Crnkovic, Paula Cristina Garcia Manoel [UNESP] (My University, 2010)
In Brazil, due to its availability, sugar cane bagasse has a high potential for power generation. The knowledge of ignition behavior, as well as the knowledge of the chemical kinetics, in of fuels combustion process is important features in boilers projects and in the stability of the combustion process control. The aim of this study is to investigate the thermal behavior of sugar cane bagasse, coal and their blends. The methodology proposed by Tognotti et al. (1985) was applied to determine the ignition temperature for all samples. Ignition temperatures were 256oC for neat bagasse and 427oC for neat coal, and 275oC for both blends (50-50% and 25-75%). The ModelFree Kinetics was applied to determine the apparent activation energy (Eα) of the thermal decomposition of sugar cane bagasse. For the two major events of mass loss of bagasse which correspond to the thermal decomposition of organic matter (mainly hemicellulose, cellulose and lignin), average values of Eα were obtained for both combustion and pyrolysis processes. In synthetic air atmosphere, the Eα were 170.8±26.3 kJ⋅mol-1 and 277.8±58.6 kJ⋅mol-1, while in nitrogen atmosphere, the Eα were 185.0 ± 11.4 kJ⋅mol-1 and 82.1±44.4 kJ⋅mol-1. The results obtained can be explained by synergistic effects when both bagasse and coal were blended, changing the fuel reactivity.
Keywords: Coal, biomass; Sugar cane bagasse; Ignition temperature; Activation energy